Between Sacrum and Profanum Tourism in Sacred Sites - Ostrowski, ks. Maciej (Turyzm/Tourism, 2005)
The author describes the theological significance of sacred sites whose primary function is as a cult, not a cultural site. He stresses the educational role of tourism as regards culture and religion while a tourism organisers’ task can be to help discover the sacrum and teach respect for it. The author is opposed to the reduction of tourism to simply sightseeing.